Multi-time Scale Adaptive Reactive Voltage Control for Distribution Networks Based on Voltage Tendency Coefficient - Ziran JIN; Hongbin WU; Yiyao ZHOU; Bin XU; Jinjin DING; Wei WEI (Zhongguo dianli)
With a high proportion of distributed photovoltaic connected to the distribution network, the mismatch between source and load may lead to voltage overlimit. Based on the deviation and fluctuation of the voltage, the voltage tendency coefficient (VTC) for evaluating different operation scenarios of the distribution network is defined and an multi-time scale adaptive reactive voltage control method is proposed in this paper. For the long time scale, a day-ahead optimal dispatch strategy aiming at the optimization of economy and security satisfaction is constructed based on VTC. And for the short time scale, the fixed slope of the traditional droop control is dynamically modified by VTC for releasing the reactive power margin of the photovoltaic inverter. In addition, a feedback correction for the long time scale is added to the short time scale optimization control. With the simulation of the example system, the effectiveness of the proposed reactive voltage control method is verified.